Dynamic regulation of neutrophil immunometabolism by platelet-derived metabolites - Mosso-Pani, Manuel Alejandro; Barreda, Dante; Salazar, Ma. Isabel (Frontiers in Immunology, 2025)
Platelets, traditionally known for their roles in hemostasis and thrombosis, have emerged as key regulators of immune responses, particularly through their dynamic interactions with neutrophils. This review explores how platelets influence neutrophil functions by forming platelet-neutrophil aggregates, releasing extracellular vesicles, and secreting metabolites. These processes govern critical immune activities, including cell recruitment, activation, endothelium interactions and the resolution or exacerbation of inflammation. Additionally, platelets induce metabolic reprogramming in neutrophils, affecting glycolysis and mitochondrial pathways, while also shaping the immune microenvironment by modulating other immune cells, such as T and B cells. Understanding this complex crosstalk between platelets and neutrophils—two of the most abundant cell types in the bloodstream—might reveal new therapeutic opportunities to regulate immune responses in inflammatory and immune-mediated diseases.